Platelet-Derived Microvesicles in Cardiovascular Diseases - Zaldivia, Maria T. K.; McFadyen, James D.; Lim, Bock; Wang, Xiaowei; Peter, Karlheinz (Frontiers in Cardiovascular Medicine, 2017)
Microvesicles circulating in the blood are small vesicles (100 nm - 1000 nm in diameter) derived from membrane blebs of cells such as activated platelets, endothelial cells and leukocytes. A growing body of evidence now supports the concept that platelet-derived microvesicles, the most abundant microvesicle in the circulation, are important regulators of hemostasis, inflammation and angiogenesis. Compared to healthy individuals, a large increase of circulating platelet-derived microvesicles has been observed, particularly in patients with cardiovascular diseases. As observed in microvesicles from other parent-cells, platelet-derived microvesicles exert their biological effects in multiple ways, such as triggering various intercellular signaling cascades and by participating in transcellular communication by the transfer of their ‘cargo’ of cytoplasmic components and surface receptors to other cell types. This review describes our current understanding of the potential role of platelet-derived microvesicles in mediating hemostasis, inflammation and angiogenesis and their consequences on the pathogenesis of cardiovascular diseases, such as atherosclerosis, myocardial infarction and venous thrombosis. Furthermore, new developments of the therapeutic potential of platelet-derived microvesicles for the treatment of cardiovascular diseases will be discussed.